The Impact of Religious Moderation Policies in Increasing Tolerance among Students in Senior High Schools - Siti Nurjannah; Abd. Madjid (Teknodika, 2026)
The application of religious moderation values in high schools remains suboptimal, as evidenced by the inconsistency between classroom instruction and students’ daily behavior. Many students continue to display intolerance, disrespectful speech, a lack of appreciation for diversity, and low participation in religious and social activities. This study aims to examine how religious moderation policies are implemented in high schools and to identify the supporting and inhibiting factors. Using a qualitative approach with the Systematic Literature Review (SLR) method based on PRISMA guidelines, data were collected from Google Scholar (2020–2024) using the keywords “religious moderation” and “high school.” Out of 5,990 articles, 21 were selected for analysis. The findings reveal that Islamic Religious Education (PAI), extracurricular activities, school culture, and interfaith approaches contribute to the implementation of religious moderation. Teacher commitment, national policies, and an inclusive school environment serve as supporting factors, while lack of parental support, negative influence of social media, and low student motivation act as barriers. Education plays a crucial role in fostering awareness and care for the school environment, creating a peaceful and just atmosphere by instilling values of tolerance, cooperation, and social responsibility in students’ daily lives.